The Role of Holy Roman Empire and Papacy in Declaration of the Armenian Kingdom of Cilicia - Hovhannisyan, Aram (History and Culture, 2023)
The article addresses a certain and very important aspect of the relations between Cilican Armenia and Holy Roman Empire – the proclamation of the Armeinan Kingdom of Cilicia and the coronation of Prince Levon II. Based on the information available in medieval Armenian and foreign historical sources, as well as the modern scientific literature of the question, the author has managed to present the international situation from the late 80s of the 12th century to 1198, the Armenian-Roman and Armenian-Byzantine relations and the process of the coronation of King Levon II. The article contains detailed information about the negotiation process between Cilician Armenia and the two powers of the time – the Holy Roman Empre and the Byzantine Empire as well as the final decisions achieved. Special attention has been attached to the religious changes offered by the Catholic Church to the Armenian Prince of Cilicia. The article also addresses the issue of the anointment of Prince Levon II and substantiates the fact that it was performed by Archbishop Conrad Wittlesbach, the representative of the Pope of Rome and the Holy Empire. Armenian Catholicos Grigor VI Apirat blessed him.
Keywords: Cilicia; political; Rome; Papacy; power; king; archbishop; Armenian Church; state; theology; religion; proclamation